COOPERATIVE PRINCIPLES IN NEGOTIATION: A CASE STUDY OF THE PULSE SHOOTING TRAGEDY - Daniel Boy Manuhuruk; Alvii T.B. Siregar (English Journal Literacy Utama, 2020)
The research is based on the case study of 911 Emergency Call